A case report of mixed acinar-endocrine carcinoma of the pancreas treated with S-1 chemotherapy: Does it work or induce endocrine differentiation?. Issue 45 (November 2017) - Yokode, Masataka; Itai, Ryosuke; Yamashita, Yukimasa; Zen, Yoh
Abstract: Rationale: Acinar cell carcinomas (ACCs) and mixed acinar-endocrine carcinomas (MAECs) of the pancreas are rare, accounting for only 1% of pancreatic tumors. Although both typically present at an advanced stage, chemotherapeutic regimes have not yet been standardized. Patient concerns: A 65-year-old man presented with a large mass in the pancreatic tail with multiple liver metastases. Diagnosis, Interventions, Outcomes: He was initially treated with gemcitabine for suspected ductal carcinoma of the pancreas, but no response was observed. S-1, administered as second-line chemotherapy, showed an approximately 38% reduction in the size of the primary tumor and metastatic deposits with therapeutic effects being maintained for 12 months. When the tumor progressed again, he underwent a percutaneous liver biopsy, which led to the diagnosis of MAEC. Combination therapy with cisplatin and etoposide targeting the endocrine component was administered, and this was based on the endocrine component potentially being less sensitive to S-1 than the ACC element. However, therapy was stopped due to the development of neutropenia, and the patient is currently receiving best supportive care. Lessons: Given the previous studies suggested that S-1 is more effective for ACCs than gemcitabine, MAECs may also respond to S-1 chemotherapy, similar to ACCs. Another potential interpretation is that S-1 was effective when the condition was ACC, and eventually showed decreased effectiveness when the condition shifted to MAEC. Future studies are needed to conclude whether S-1 chemotherapy truly works against MAECs or induces endocrine differentiation in ACCs as a part of the drug-resistance process.